2017
DOI: 10.1128/aem.01378-17
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Shiga Toxin-Encoding Prophage by Abiotic Environmental Stress in Food

Abstract: The prophage-encoded Shiga toxin is a major virulence factor in Stxproducing Escherichia coli (STEC). Toxin production and phage production are linked and occur after induction of the RecA-dependent SOS response. However, foodrelated stress and Stx-prophage induction have not been studied at the single-cell level. This study investigated the effects of abiotic environmental stress on stx expression by single-cell quantification of gene expression in STEC O104:H4 Δstx2::gfp:: amp r . In addition, the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 57 publications
0
37
0
Order By: Relevance
“…Although bacteriocin production is usually induced in vitro by DNA damaging agents, which trigger SOS response leading to the production of bacteriocins (10, 14), it is possible that bacteria can produce bacteriocins in planta . In support of this hypothesis, recent studies have shown that bacterial SOS can be triggered directly or indirectly by different factors such as nutrient starvation, iron deficiency, chromate stress, acidic and alkaline stress, oxidative stress and β-lactam antibiotics (10, 66-69). All the above scenarios can be encountered by Pcb in planta , for example, one of the first stresses encountered by Pcb , SREs and other endophytes in potato tubers is acidic pH, which SREs must neutralize to be able to produce PCWDEs (65, 70, 71).…”
Section: Discussionmentioning
confidence: 89%
“…Although bacteriocin production is usually induced in vitro by DNA damaging agents, which trigger SOS response leading to the production of bacteriocins (10, 14), it is possible that bacteria can produce bacteriocins in planta . In support of this hypothesis, recent studies have shown that bacterial SOS can be triggered directly or indirectly by different factors such as nutrient starvation, iron deficiency, chromate stress, acidic and alkaline stress, oxidative stress and β-lactam antibiotics (10, 66-69). All the above scenarios can be encountered by Pcb in planta , for example, one of the first stresses encountered by Pcb , SREs and other endophytes in potato tubers is acidic pH, which SREs must neutralize to be able to produce PCWDEs (65, 70, 71).…”
Section: Discussionmentioning
confidence: 89%
“…For other parameters commonly used in the food industry, Aertsen et al (2005) found that high pressure used in food processing had little effect on the induction of Stx2-encoding prophage from several environmental STEC isolates. Another study also indicated that heat treatment in food preservation was not able to induce Stx2 prophage from the E. coli O104:H4 strain, which was related to the 2011 outbreak in Germany (Fang et al, 2017). The authors also found that H 2 O 2 , typically used as an antimicrobial agent, was able to induce Stx prophage from the strain through the SOS response mechanism.…”
Section: Discussionmentioning
confidence: 98%
“…Different studies have reported the detection of STEC by PCR or qPCR from different matrices [35][36][37][38] and the challenges of subsequently obtaining cultured STEC isolates. This significant discrepancy may be related to dead and injured cells, cells in a viable but non-culturable (VBNC) state, the presence of free DNA and free Stx bacteriophages in the samples [10,[39][40][41][42][43][44]. In addition, the microbial communities can have an important influence on the survival capabilities of STEC in environmental substrates and consequential cultural isolation [24,45].…”
Section: Discussionmentioning
confidence: 99%